Access to health infrastracture and child health development: Evidence from post-apartheid South Africa - Shinsuke Tanaka (Osaka University, Institute of Social and Economic Research (ISER), 2010)
A growing body of literature shows that child health has substantial long-term economic impacts. This study examines whether, and to what extent, increased access to health infrastructure leads to better child health status as measured by weight-for-age z-scores. To assess the causal relationship, I exploit plausibly exogenous variation in access induced by the dramatic change in health policy in South Africa immediately after the end of apartheid. Using longitudinal household data, health services are found to improve the nutritional status of not only newly born babies but also children who were already born at low health status. Yet, the effects are significant only for boys.
Additional information: The 12th ISER-Moriguchi Prize (2009) Awarded Paper.
Keywords: I18; H54; J13; H51; O15; 330; child health; health infrastructure; South Africa; Kinder; Gesundheit; Gesundheitsversorgung; Südafrika